Retratos de um cenário oitocentista na província do Espírito Santo (1845-1888): Crimes e Escravidão - Camara, Raphael Americano (2019)
The present research aims to discuss the daily social relations experienced in the District of Vitória/ES, in the second half the 19th century, more precisely between 1850 and 1899, by slaves and freemen. By means of the reading of the hearings and testimonials of defendants, victims and witnesses, belonging to the collection of the Public Archive of the State of Espírito Santo, we seek to understand the dynamics of the local society by examining the relations of proximity, friendship, enmity, sympathy and violence, as well as the affective engagements that were established in the day by day of freemen, of slaves and of freed slaves. We have also used as sources messages from the president of the province as well as journals of the province of Espírito Santo. As for the methodology, we have aimed to take possession of Carlo Ginsburg’s teachings, seeking to find, through clues, signs and indictments, elements that would enable us to interpret the daily aspects experienced by the inhabitants of the District of Vitória/ES.As our conclusion, we were able to verify the diversity and the complexity that pervaded the daily life of freemen and slaves in the province of Espírito Santo, where violence was constantly present, along with the possibility of a closer interaction between masters and slaves.